OPTIMISM AND THE PROBLEM OF TIME (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Human life always develops from the past - through the present - to the future. Therefore, the study of a person's life path is inextricably linked with the study of how they perceive time in a personal-psychological context.